Aztreonam for febrile neutropenia in patients with beta‐lactam allergy. Issue 1 (14th October 2013) - McCullough, B.J.; Wiggins, L.E.; Richards, A.; Klinker, K.; Hiemenz, J.W.; Wingard, J.R.
Abstract Background Beta‐lactam antibiotics are the mainstay of empiric therapy for febrile neutropenia. Aztreonam may benefit certain patients because of a lack of cross‐hypersensitivity to penicillins and cephalosporins. This is the first study, to our knowledge, to evaluate the efficacy of aztreonam as monotherapy for febrile neutropenia (FN). Methods Our study was a single‐center retrospective chart review of patients ≥18 years of age receiving aztreonam for the treatment of FN. Primary outcome was treatment success of aztreonam monotherapy. Secondary analyses included need for modification to antimicrobial therapy, patients transitioned to aztreonam from another empiric regimen, and patients receiving aztreonam in combination with other antibacterial agents. Results In patients prescribed aztreonam for first fever, 11 of 27 (40.7%) patients who received aztreonam alone and 19 of 40 (47.5%) given aztreonam plus another antibiotic responded within 96 h (P = 0.62). Twenty‐four (89%) patients prescribed aztreonam monotherapy were alive when FN resolved or treatment ended. Infectious mortality was low (1 patient, 3.7%). In patients prescribed aztreonam monotherapy following an adverse reaction to cefepime, 6 of 11 (54.5%) responded within 96 h of initiating aztreonam; 10 (91%) were alive when FN resolved or treatment ended. Conclusion Aztreonam monotherapy may be acceptable for use in patients with a history of beta‐lactam hypersensitivity or following an adverse reaction with another beta‐lactam. Further studies are needed to compare efficacy of aztreonam monotherapy with other therapies for the treatment of FN.